Peran Pola Asuh Orang Tua di Era Digital Terhadap Bahaya Pornografi Pada Otak Anak - Kodariyah Nurhayat; Kasmanah; Djoni Aminudin (SAMBARA: Jurnal Pengabdian Kepada Masyarakat, 2023)
The role of parents in children's education is a serious and important thing today. Among the roles of parents in education today is to accompany children and adolescents so that they can fortify themselves from the bad influence of media digitalization. Currently, children are spoiled by information and communication technology (ICT). The internet has become a basic need for children today, especially as students. School assignments require them to search for many references on the internet. This is one of the positive impacts of the internet. However, it is like a double-edged sword. The internet also has a negative impact if misused by children. Freedom to access internet sites that have negative impacts such as violent videos leading to bullying, porn, and so on can lead children themselves astray if without parental supervision. Therefore, a psychological study on proper parenting in the Digital Era regarding the Dangers of Pornography to the Brain is very necessary. For this reason, the Community Service Team (PkM) will provide educational counseling and information services to parents of the Indonesian Family House (RKI) Makasar, East Jakarta at Insan Madani Elementary School, Makasar District, East Jakarta with a target of 100 parents of students. Community service activities will be held on Saturday, May 13, 2023, at 08.00 - 11.00 WIB. Located in the School Hall. The results of this activity show an increase in insight, knowledge, and the right attitude in accompanying children when using social media. Evidenced by changes in direction and positive behavior in planning assistance, teaching, giving advice to children when using social media in order to keep them away from the dangers of pornography on children's brains.